The Connotation Meaning of Social Problems in the Movie “Agak Laen” - Priadi, Rizal; Hendri, Ridar; Salam, Noor Efni; Pratiwi, Rosi (Journal of English Language and Education, 2025)
This study explores the connotative meanings of various social problems as depicted in the Indonesian horror-comedy film Agak Laen through the lens of Roland Barthes’ semiotic theory. By applying Barthes' framework—denotation, connotation, and myth—this research identifies and analyzes the layered symbolic representations of poverty, gratification, crime, infidelity, and social inequality in selected film scenes. Using a qualitative descriptive method, supported by content analysis and semiotic interpretation, the study reveals how non-verbal cues, visual composition, and character dialogue convey implicit social criticism. The findings indicate that Agak Laen does more than entertain; it reflects structural issues within Indonesian society and offers a satirical critique of moral dilemmas, class divides, and systemic corruption. These connotative messages, embedded within comedic and horror narratives, function as powerful tools for audience reflection and social commentary. The film thus becomes not only a medium of entertainment but also a form of cultural discourse that challenges viewers to engage with the underlying societal issues presented on screen.